2012
DOI: 10.1007/s10722-011-9785-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Chinese white pear cultivars using SSR markers

Abstract: 109 Pyrus accessions including 92 local Chinese accessions of P. bretschneideri were identified genetically using nine microsatellite loci developed from apple and pear. The nine SSR loci revealed 129 alleles in 109 pear accessions and 114 alleles in 92 Chinese white pears. Among the 92 local Chinese accessions of P. bretschneideri, 70 could be differentiated successfully except for 10 sets of synonymous or mutants. For the 92 accessions, the number of putative alleles per locus ranged from seven to 18, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 29 publications
1
6
0
1
Order By: Relevance
“…The apple locus CH02B12 revealed the highest allele numbers (27), while the pear locus KA14 yielded the lowest numbers (9). In agreement with this study, KA14 was also reported previously to generate low allele numbers (three alleles) (Katayama et al , ; Tian et al , ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The apple locus CH02B12 revealed the highest allele numbers (27), while the pear locus KA14 yielded the lowest numbers (9). In agreement with this study, KA14 was also reported previously to generate low allele numbers (three alleles) (Katayama et al , ; Tian et al , ).…”
Section: Discussionsupporting
confidence: 93%
“…DNA marker technologies such as random amplified polymorphic DNA (RAPD) and amplified fragment length polymorphisms (AFLP) have been employed for genetic characterisation of pears (Iketani et al , ; Monte‐Corvo et al , ; Teng et al , ; Manganaris & Tsipouridis, ; Monte‐Corvo et al , ; Kim et al , ; Bao et al , ). More recently, simple sequence repeats (SSRs or microsatellites) have emerged as a powerful tool for DNA fingerprinting of pear germplasm due to their hyper‐variability, co‐dominance, high reproducibility and relative abundance (Powell et al , ; Yamamoto et al , 2001, 2002 a ; Brini et al , ; Erfani et al , ; Tian et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis SSR markers were used for identification of Chinese white pear cultivars and they were found ideal marker systems for phylogenetic reconstruction in pear species (Tian et al 2012). On the basis of allele sharing and Jaccard's similarity matrix, UPGMA dendrogram inferred two major groups of all pear accessions.…”
Section: Ssr Diversity and Structurementioning
confidence: 99%
“…However, the authors converted the specific RAPD molecular markers into SCAR, which indicated its practical application and utility as a good reference for further research. Different identification methods have been report by Tian et al (2012), who used 9 SSR markers to identify 109 pear accessions, including 92 local Chinese accessions of Pyrus bretschneideri based on clusters directly obtained from the UPGMA dendrogram. Similar results were obtained by Madhou et al (2013), who used 11 SSR loci to fingerprint and identify cultivars of 88 litchi accessions, based on the UPGMA dendrogram, contributing to the rapid identification of cultivars based on a high distances of the GS coefficient between cultivars.…”
Section: Samplesizeselectionandfingerprintingconstructionmentioning
confidence: 99%